Keys factor affecting employee performance in the banking sector: a Delphi study - Cairson Ng; Walton Wider; Chunwen Yang; Leilei Jiang; Asokan Vasudevan; Pratikshya Bhandari; Harvey Pak Ting Lee (Cogent Business & Management, 2024)
This study investigates the key factors influencing employee performance in the banking sector, focusing on how traditional and emergent challenges affect workforce efficiency and satisfaction. Given the rapidly evolving digital landscape, the research seeks to identify the most significant determinants of employee performance that banking institutions must address to maintain stability and growth. The study employs the Delphi Method, engaging a panel of 29 experts through two rounds of surveys to identify and rank the determinants of employee performance. This iterative process allowed for the refinement of expert insights, ultimately leading to a consensus on the most impactful factors influencing performance in the banking sector. The results indicate that compensation and benefits are the most critical factors affecting employee performance, followed by organizational culture and working environment, leadership and management, job satisfaction and motivation, and work-life balance and flexibility. The study highlights that while compensation is paramount, work-life balance and flexibility, though important, have a lower immediate impact on performance. This research contributes to the theoretical framework of employee performance by integrating contemporary challenges specific to the banking sector with broader motivational theories, such as Maslow's Hierarchy of Needs. The study provides practical insights for banking institutions, emphasizing the need for holistic strategies that address employee well-being and organizational objectives. These findings offer valuable guidance for stakeholders to enhance productivity and employee satisfaction in the competitive banking industry.
Keywords: 650; Employee performance; banking sector; workforce; Delphi method; economic growth